Shocks, livestock assets and climate change adaptation in Kenya - Ngigi, Marther W.; Birner, Regina (My University, 2013)
The study assesses the impact of shocks on livestock and the role of adaptation to climate change in protecting assets from weather shocks. Data collection relied on a mixed-method approach, including household surveys and participatory rural appraisals (PRAs) in each site. The study uses panel data collected in 2009 and 2012 and a total of 362 balanced panels are used in the study. The study uses fixed effect models in analysis. The findings show that shocks have a negative effect on livestock. Small and large animals are affected differently by different shocks. Large livestock are mostly affected by droughts while market shocks affect small animals. The study also finds that land ownership and income positively affect livestock assets. With regard to adaptation to climate change, farmers who are adapting to changing climate are resilient to weather shocks. Membership in community-based organizations help households in accumulating livestock assets, and this suggests the importance of local institutions in risk management. The study also discusses policy implications.
Keywords: Shocks; Livestock; Adaptation; Climate change; Kenya